Sustainable Cooperative System based on Self-Management: Empowerment of "Gambuh" All-Business Cooperative Gongseng Megaluh Jombang - Izzatul Umami; Rizka Mudyanti; Linda Rata Sari; Agus Raikhani (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
In Indonesia, cooperatives play a role in improving economic and social welfare and play an active role in improving the quality and standard of living of people and society. Currently, many cooperatives are still run manually even though the development of information systems has made very rapid progress. This information system technology can create an online-based cooperative system, making it easier and more efficient to work. The system is built by using MySQL as a database. This research uses a Research and Development (RD) approach with seven stages: research, planning, development, Preliminary field testing, Main product revision, and Main field testing and testing. This system needs a model designed using Unified Modelling Language (UML), which is depicted through use case diagrams and activity diagrams. Testing this cooperative system uses the Black Box Testing method. Black box testing, also called Behavioral Testing, is a test carried out to observe the input and output results of the software without knowing the code structure of the software.